Ovarian cancer patients' and their family members' perspectives on novel vaccine and virotherapy trials. (December 2016) - Radecki Breitkopf, Carmen; Ridgeway, Jennifer L; Asiedu, Gladys B; Carroll, Katherine; Tenney, Meaghan; Jatoi, Aminah
Background/aims: Some of the most promising avenues of cancer clinical investigation center on immunotherapeutic approaches. These approaches have provided notable gains in cancer therapeutics with recent Food and Drug Administration approvals of agents of this class in several types of cancers, although gains for ovarian cancer lag behind. This study examined perceptions of therapeutic trials including immunotherapy and virotherapy among ovarian cancer patients and their family members. Methods: A total of 72 semi-structured qualitative interviews were conducted with 33 patients and 39 family members at two National Cancer Institute–designated comprehensive cancer centers. Eligible patients were diagnosed with epithelial ovarian, primary peritoneal, or fallopian tube carcinoma and had experience with clinical trial conversations; family members were nominated by patients and interviewed separately. Applied thematic analysis was used to understand and interpret the data. Results: More participants were aware of vaccine trials than virus trials, although more than half had heard of at least one of them. Initial reactions to vaccine trials were generally favorable. For many, childhood experience with vaccines lent a familiar frame of reference. Virus trials elicited more negative initial reactions, including the use of adjectives such as "scary" and "dreadful." Viruses seemed contagious or difficult to control. Increased receptivity to these trials occurred in the context of limited therapeutic options and cancer recurrence. Most participants, including those not immediately drawn to these types of trials, indicated openness to learning more. Conclusion: Although vaccine and viral trials are both immunologically based therapeutic approaches, patients who are offered these trials may perceive their potential benefit and safety quite differently. There is a need to consider terminology, solicit and address "gut reactions, " and provide information that enables patients and their family members to better understand the science behind these trials.